Why do health-risk awareness and materialism drive consumers' acceptance intentions for smart green buildings? - Chu, Lydia (Frontiers in Psychology, 2024)
As the threat of global warming to human beings has gradually received attention, this article introduces the terror management theory to explain whether health risk awareness will affect their willingness to accept smart green buildings and that relationship is positively regulated by death anxiety. In addition, this article introduces the concept of materialism to propose that consumers will also accept smart green buildings due to the influence of materialism. This article interviewed two consumers and two professors in Taiwan, and verified the three hypotheses of this article through qualitative coding analysis. This article also used quantitative research methods to verify the theoretical model. This article not only introduces the cross-cutting contributions between terror management theory, materialism and smart green buildings, but also helps the construction industry develop strategies to attract consumers.